Direitos humanos e democracia: fundamentação filosófica em Jürgen Habermas - Oliveira, Francielle Vieira (2010)
This dissertation aims to analyze the philosopher Jürgen Habermas's contributions to issues of human rights and democracy, based on the works Inclusion of the Other, The Post-National Constellation, Law and Democracy. It is intended to show the relevance of the subject both nationally and internationally, against the political, economic and social, that are imposed by today's globalization. This work also aims to demonstrate the importance of actions against the disrespect to human beings and their freedom of participation and emphasize the need to promote the inclusion of those who are marginalized by the system, which colonizes the lifeworld (Lebenswelt). An approach to the origin of human rights is first made since its naturalistic design, through rationalization, confronting the limits of morality, to gain legitimacy in the legal discourse. Next, we seek to examine how we can make the construction of democratic and legitimate rule of law, weaving critical to the deliberative model proposed by Habermas. Then, we suggest alternatives to the participation of citizens in the Legislative, Executive and Judicial. The notion of popular sovereignty in the "post-national" States will be questioned here mainly in relation to the lack of legitimacy in the decisions of supra-state levels and outcome of the agenda of Habermas for inclusion in the formation of a Federation of States. The formation of blocs still seems, however, the mandatory exit to avoid the devastating effects of market, culture and world politics internationalization. Resume, then, Habermas' theory of communicative action and also of the democratic principle, in the scope of peace promotion, face the horrors of war, especially the Iraq war that intensified after the attacks on the United States on September 11, 2001. Finally, we discuss the formation of a global society and the effects deriving from it relating to the themes of universalism and relativism of human rights and the difficulties that confront the inclusion of "other."